Strategi Kepala Sekolah Dalam Meningkatkan Kreativitas Guru dan Siswa Berbasis Kearifan Lokal di Sekolah Dasar - Aida Rosni; Zikrur Rahmat; Zahraini Zahraini (Faculty of Social Science, Universitas Negeri Padang, 2026)
This study is motivated by the important role of the principal in creating a conducive learning environment to enhance teacher and student creativity through local wisdom, which has not been optimally utilized at SDN 2 Samadua. The objectives are to analyze the principal’s role, identify internal and external factors, and formulate strategies to improve creativity based on local wisdom using SWOT analysis. The research employs a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation, and analyzed using IFAS, EFAS, and SWOT techniques. The findings indicate that the principal plays a central role in fostering creativity through innovative leadership, teacher commitment, and the utilization of local cultural potential and community support. Existing weaknesses and threats can be addressed through appropriate strategies. In conclusion, the development of creativity based on local wisdom depends on innovative and collaborative school leadership, strengthening teacher capacity, and optimizing external opportunities, with SWOT-based strategies serving as practical guidelines to improve learning quality.